(untitled) (Nepal Journal of Environmental Science, 2023)
The enzymes are having wide applications in various industries. The group of microorganisms, viz., bacteria, fungi, actinobacteria produces different enzymes, viz., cellulase, chitinase, amylase, protease, lecithinase, lipase, gelatinase, etc. and these enzymes have immense market demand. The work here describes isolation of Trichoderma sp. and study of their colony characteristics on different agar media. The morphology images of Trichoderma sp. were also studied light and stereo microscope. The isolated Trichoderma sp. was studied for the production of cellulase. The isolated three species of Trichoderma were found to show production of cellulase. The cellulase production was more by Trichoderma sp. isolate No. 1. The cellulase production by Trichoderma sp. will have applications in food and other industries. The production of cellulase by Trichoderma sp. will be economical and eco-friendly.